PERILAKU INFORMASI PARA PENGGALI EMAS TRADISIONAL (GURANDIL) DALAM MELAKUKAN KEGIATAN EKSPLORASI DAN PENGOLAHAN TAMBANG EMAS - Silvana, Tine; Winoto, Yunus (Universitas Padjadjaran, 2015)
In this study researchers are interested to examine how the behavior of information among the traditional gold mining or